Negative active material, preparation method thereof and battery

A high-performance phosphorus-doped graphite anode material was prepared by mixing and carbonizing high-sulfur petroleum coke, isotropic coke, organic titanium-based crosslinking agent and binder, and coating the graphite surface with phosphorus and molybdenum sulfide compounds. This solved the problem of insufficient cycle and rate performance of existing lithium-ion battery anode materials and achieved a significant improvement in battery performance.

CN120895654AActive Publication Date: 2025-11-04HUNAN LIHENG NEW MATERIALS CO LTD

Patent Information

Application Number
CN202511416632.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-30
Publication Date
2025-11-04
Estimated Expiration
2045-09-30

AI Technical Summary

Technical Problem

Existing lithium-ion battery anode materials have shortcomings in terms of cycle performance and rate performance, especially when using graphite anode materials prepared from high-sulfur petroleum coke.

Method used

After carbonization by mixing high-sulfur petroleum coke, isotropic coke, organic titanium-based crosslinking agent and binder, phosphine doping is introduced and molybdenum sulfide and lithium benzenesulfonate compound are coated on the graphite surface to form a phosphorus-doped graphite anode material. Titanium-doped amorphous carbon is formed by using organic titanium-based crosslinking agent to improve the material performance.

Benefits of technology

It significantly improves the cycle performance and rate performance of lithium-ion batteries, enhances the fast charging performance and structural stability of batteries, increases the adhesion and tap density of negative electrode materials, and reduces battery impedance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120895654A_ABST
    Figure CN120895654A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrochemistry, and particularly provides a negative electrode active material, a preparation method thereof and a battery. The preparation method of the negative electrode active material comprises the following steps: mixing the high-sulfur petroleum coke, the isotropic coke, the organic titanium-based cross-linking agent and the binder, and carbonizing at the temperature of 300-500 DEG C; after carbonization is completed, the temperature is raised to 1000-1200 DEG C, then phosphorane is introduced, the phosphorus element is doped into the carbonized material, and a phosphorus-doped graphite precursor is obtained; graphitizing the phosphorus-doped graphite precursor to obtain phosphorus-doped graphite; and soaking the phosphorus-doped graphite in an organic solution containing molybdenum sulfide and a lithium benzenesulfonate compound, and drying to obtain the negative electrode active material. The negative electrode active material obtained by the preparation method can significantly improve the cycle performance and the rate capability of the battery, and the molybdenum sulfide and the lithium benzenesulfonate compound coated on the surface of the graphite can further improve the low temperature resistance and the high temperature resistance of the negative electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of electrochemistry, in particular to a negative electrode active material, a preparation method thereof and a battery. BACKGROUND

[0002] The performance of a negative electrode material, which is an important component of a lithium ion battery, is mainly determined by raw materials. Currently, the raw materials for preparing the negative electrode material are mainly petroleum coke, needle coke and pitch coke, which are sequentially carbonized, graphitized and granulated. The selection of the raw materials has an important influence on the specific capacity, cycle life, rate capability and tap density of the battery. In a traditional preparation scheme, high-sulfur petroleum coke is used as a raw material to prepare a graphite negative electrode material. However, when the graphite negative electrode material is applied to a lithium ion battery as a negative electrode, the lithium ion battery still has the problems of poor cycle performance and rate capability. SUMMARY

[0003] Therefore, it is necessary to provide a preparation method of a negative electrode active material, which can significantly improve the cycle performance and rate capability of a battery. Furthermore, a negative electrode active material and a battery are also provided.

[0004] The first aspect of the present application provides a preparation method of a negative electrode active material, comprising the following steps: mixing high-sulfur petroleum coke, isotropic coke, an organic titanium-based crosslinking agent and a binder, and then carbonizing at 300-500°C; after the carbonization is completed, the temperature is raised to 1000-1200°C, and then phosphine is introduced to dope phosphorus elements into the carbonized material, to obtain a phosphorus-doped graphite precursor; graphitizing the phosphorus-doped graphite precursor to obtain phosphorus-doped graphite; immersing the phosphorus-doped graphite in an organic solution containing a molybdenum sulfide and a lithium benzenesulfonate compound, and drying to obtain a negative electrode active material.

[0005] In some embodiments, the mass ratio of the high-sulfur petroleum coke, the isotropic coke, the organic titanium-based crosslinking agent and the binder is 100: (50-200): (5-20): (2-10).

[0006] Preferably, the S content of the high-sulfur petroleum coke is 3-6 wt%.

[0007] In some embodiments, the binder is selected from pitch and unsaturated resin; the pitch is selected from one of medium-temperature pitch and high-temperature pitch; the unsaturated resin is selected from at least one of bisphenol A type vinyl unsaturated polyester and isophthalic acid type vinyl unsaturated resin; and the mass ratio of the pitch to the unsaturated resin is 1: (0.2-5).

[0008] In some embodiments, the method for introducing phosphoranes comprises: mixing phosphoranes with nitrogen, and then introducing the mixed gas; the volume ratio of phosphoranes to nitrogen is (1-5):10; the total flow rate of the mixed gas introduced is 100 mL / min-500 mL / min; the time for introducing the mixed gas is 30 min-300 min.

[0009] In some embodiments, the preparation method satisfies at least one of the following conditions: (1) the carbonization time is 2 h-12 h; (2) the graphitization time is 2 h-12 h; (3) the graphitization temperature is 2800℃-3200℃.

[0010] In some embodiments, the preparation method of the organic titanium-based crosslinking agent comprises the following steps: mixing titanium ester, ethylene glycol, organic acid and hydroxybenzaldehyde compound in a mass ratio of (5-15):100:(10-30):(10-30), and then reacting at a temperature of 50℃-100℃ for 2 h-12 h; filtering and vacuum drying to obtain the organic titanium-based crosslinking agent; the titanium ester is selected from one of tetrabutyl titanate, tetraisopropyl titanate, tetra-2-methyl-2-butanol titanate and n-propyl titanate; the organic acid is selected from one of benzoic acid, p-aminobenzenesulfonic acid, tartaric acid, oxalic acid, malic acid, citric acid and ascorbic acid; the hydroxybenzaldehyde compound is selected from one of m-hydroxybenzaldehyde, 2,5-dihydroxybenzaldehyde, 3,4-dihydroxybenzaldehyde, 2,3-dihydroxybenzaldehyde, 2-hydroxy-5-methylbenzaldehyde and 2-hydroxy-4-methylbenzaldehyde.

[0011] In some embodiments, the preparation method satisfies at least one of the following conditions: (1) the lithium benzenesulfonate compound is selected from one of 4-methyl lithium benzenesulfonate, 3-(diphenylphosphino) lithium benzenesulfonate, 4-(diphenylphosphino) lithium benzenesulfonate and polyvinyl lithium benzenesulfonate; (2) the organic solvent in the organic solution is selected from one of diethyl ether, dipropyl ether, diisopropyl ether, ethyl butyl ether, dibutyl ether, dipentyl ether and diisopentyl ether; (3) the organic solution further comprises a dispersant; the dispersant is selected from one of polyisobutylene succinate, propylene glycol methyl ether acetate and styrene-acrylic acid copolymer; preferably, the mass ratio of the dispersant to the phosphorus-doped graphite in the organic solution is (1-5):100; (4) the mass concentration of the molybdenum sulfide in the organic solution is 1wt%-10wt%; (5) The mass concentration of the lithium benzenesulfonate compound in the organic solution is 1wt%-10wt%.

[0012] The second aspect of the present application provides a negative electrode active material, which is prepared according to the preparation method provided in the first aspect of the present application; or the negative electrode active material comprises a core and a shell layer arranged on the surface of the core, the core comprises phosphorus-doped graphite, and the shell layer comprises molybdenum sulfide and a lithium benzenesulfonate compound.

[0013] In some embodiments, the mass fraction of the shell layer in the negative electrode active material is 2wt%-5wt% based on 100% of the total mass of the negative electrode active material.

[0014] The third aspect of the present application provides a battery, which comprises a positive electrode, a negative electrode, an electrolyte and a separator, wherein the negative electrode comprises the negative electrode active material prepared according to the preparation method provided in the first aspect of the present application, or the negative electrode comprises the negative electrode active material provided in the second aspect of the present application.

[0015] Advantages:

[0016] (1) In the above preparation method, high-sulfur petroleum coke and isotropic coke are used as the coke source, and cross-linking and bonding mixing are carried out under the action of an organic titanium-based cross-linking agent and a binder, and then carbonization and graphitization treatment are carried out; wherein the high-sulfur petroleum coke has good kinetic performance and can improve the fast-charging performance, and the isotropic coke has the characteristics of low expansion rate and good cycle performance, so that the advantages of the two can be synergistically exerted to improve the cycle performance and power performance of the battery at the same time. At the same time, the organic titanium-based cross-linking agent is used, and titanium-doped amorphous carbon is formed after carbonization, which can improve the fast-charging and cycle performance of the battery by relying on the large interlayer spacing characteristics of titanium itself.

[0017] (2) Under the condition of 1000℃-1200℃, phosphine is introduced to make the phosphine crack to generate elemental phosphorus doped in the pore holes and on the surface of the graphite precursor, which can further improve the specific capacity of the graphite negative electrode material by relying on the high specific capacity characteristics of phosphorus, and thus improve the discharge specific capacity of the battery.

[0018] (3) The graphite surface is coated with molybdenum sulfide and a lithium benzenesulfonate compound, which can improve the solvation ability of the negative electrode material by relying on the strong solvation ability of the sulfonic acid group in the lithium benzenesulfonate organic compound and the strong solvation ability of the molybdenum sulfide inorganic compound, and thus improve the lithium ion intercalation and deintercalation rate in the charging and discharging process of the battery, improve the rate performance and cycle performance; at the same time, the phenyl group grafted on the surface of the sulfonic acid compound has a stable structure, which can improve the cycle performance of the battery. Further, the graphite surface is coated with molybdenum sulfide and a lithium benzenesulfonate compound at the same time, which can further improve the structural stability of SEI in the charging and discharging process of the battery and improve the low-temperature resistance and high-temperature resistance of the material by the mutual synergy of the two.

[0019] (4) The binder in the present application uses asphalt and unsaturated resin. The unsaturated resin binder contains unsaturated double bonds, which are easy to form cross-linking structures, thereby improving the bonding force between materials. After carbonization, soft carbon can be formed, which can synergize with the hard carbon generated by the carbonization of unsaturated resin to improve the adhesion of the graphite negative electrode active material, thereby improving the tap density of the negative electrode active material and reducing the impedance. BRIEF DESCRIPTION OF DRAWINGS

[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings needed in the embodiments of the present application will be briefly introduced as follows. Obviously, the drawings described below are only some embodiments of the present application, and other drawings can be obtained by those skilled in the art without creative labor on the basis of the drawings.

[0021] Figure 1 SEM image of the negative electrode active material prepared in Example 1. DETAILED DESCRIPTION

[0022] The embodiments described in the specification are only for the purpose of explaining the present application, and are not intended to limit the present application.

[0023] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit can be combined with any upper limit to form a range not explicitly recited; and any lower limit can be combined with other lower limits to form a range not explicitly recited, as can any upper limit with any other upper limit. Furthermore, although not explicitly recited, every point or individual number between the range endpoints is included in the range. Thus, every midpoint between outer limits is also included. Each point or individual number can serve as its own lower limit or upper limit to combine with another point or individual number or with a range endpoint. Consequently, every point or individual number can serve as its own lower limit or upper limit to combine with another point or individual number or with a range endpoint.

[0024] The present application will be further described in conjunction with the following examples. It should be understood that these examples are only for illustrative purposes, and various modifications and changes within the scope of the present application disclosed herein will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages and ratios reported in the following examples are based on mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and used directly without further purification, and the instruments used in the examples are commercially available. In particular, the raw materials used in each embodiment and the information thereof are as follows: The high-sulfur petroleum coke used is from Xinjiang Tahe Petrochemical Co., Ltd. of Sinopec, and its S content is 3wt%-6wt%.

[0025] Isotropic coke: Anshan Thermal Energy Research Institute Co., Ltd.

[0026] Medium temperature pitch: Liaoning Xinde Co., Ltd.; softening point 70-90℃.

[0027] High temperature pitch: Liaoning Xinde Co., Ltd.; softening point 180℃; model: 180#.

[0028] Mesophase pitch: Jinan Chaolian New Material Technology Co., Ltd.; model: 8175.

[0029] Bisphenol A type vinyl unsaturated polyester: Changzhou Tianma Group; model: TM3301.

[0030] Isophthalic acid type vinyl unsaturated resin: Shandong Kaiwei New Material Co., Ltd.

[0031] Styrene-acrylic acid copolymer: Wuhu Fuguan New Material Co., Ltd.

[0032] Example 1

[0033] Preparation of organic titanium-based crosslinking agent: A three-necked flask was added with 10 g of tetrabutyl titanate, 100 g of ethylene glycol, 20 g of p-aminobenzenesulfonic acid and 20 g of benzaldehyde, and reacted at 80℃ for 6 h. The obtained material was dried at 80℃ under vacuum for 24 h to obtain an organic titanium composite crosslinking agent.

[0034] Preparation of negative electrode active material from composite coke raw material: Step S1, 100 g of high-sulfur petroleum coke, 100 g of isotropic coke, 10 g of organic titanium-based crosslinking agent and 3 g of medium temperature pitch, 3 g of bisphenol A type vinyl unsaturated polyester were mixed uniformly, and were subjected to 6 h of heat preservation treatment at 400℃, and then were heated to 1100℃, and a mixed gas of phosphine and nitrogen (volume ratio, phosphine: nitrogen = 3: 10) was introduced at a total flow rate of 300 mL / min for 150 min, and then the obtained composite coke material was heated to 3000℃ for 48 h of high temperature graphitization to obtain a graphite material.

[0035] Step S2, 3 g of 4-methylbenzenesulfonic acid lithium, 3 g of molybdenum sulfide were added to 120 g of ethyl ether organic solvent to configure a solution, and then 3 g of polyisobutylene succinate, 100 g of graphite material were dispersed uniformly; spray drying was performed, the drying medium inlet temperature was 220℃, the outlet temperature was 80℃, the flow rate was 0.2 kg / h, and the drying time was 5 h to obtain a negative electrode active material.

[0036] Example 2

[0037] Preparation of organic titanium-based crosslinking agent: Into a three-necked flask, 5 g of tetrabutyl titanate, 100 g of ethylene glycol, 10 g of p-aminobenzenesulfonic acid and 10 g of 2,5-dihydroxybenzaldehyde were added, and reacted at 50°C for 12 h, filtered, and the obtained material was dried at 80°C under vacuum for 24 h to obtain an organic titanium composite crosslinking agent.

[0038] Preparation of negative electrode active material from composite coke raw material: Step S1: 100 g of high-sulfur petroleum coke, 50 g of isotropic coke, 5 g of organic titanium-based crosslinking agent and 1 g of high-temperature pitch, and 1 g of isophthalic acid type vinyl unsaturated resin were uniformly mixed, and heat treated at 300°C for 12 h, and then heated to 1000°C, and a mixed gas of phosphine and nitrogen (volume ratio, phosphine:nitrogen=5:10) was introduced at a total flow rate of 100 mL / min for 300 min, and then the obtained composite coke material was heated to 2800°C for graphitization for 48 h to obtain a graphite material.

[0039] 1 g of lithium 3-(diphenylphosphino)benzenesulfonate and 1 g of molybdenum sulfide were added to 200 g of dipropyl ether to form a solution, and then 1 g of propylene glycol methyl ether acetate and 100 g of graphite material were uniformly dispersed; spray drying was performed, the drying medium inlet temperature was 220°C, the outlet temperature was 80°C, the flow rate was 0.2 kg / h, and the drying time was 5 h to obtain a negative electrode active material.

[0040] Example 3

[0041] Preparation of organic titanium-based crosslinking agent: Into a three-necked flask, 15 g of tetrakis-2-methyl-2-butanol titanate, 100 g of ethylene glycol, 30 g of tartaric acid and 30 g of 3,4-dihydroxybenzaldehyde were added, and reacted at 100°C for 2 h, filtered, and dried at 80°C under vacuum for 24 h to obtain an organic titanium composite crosslinking agent.

[0042] Preparation of negative electrode active material from composite coke raw material: Step S1: 100 g of high-sulfur petroleum coke, 200 g of isotropic coke, 20 g of titanium-based crosslinking agent, 5 g of mesophase pitch and 5 g of isophthalic acid type vinyl unsaturated resin were uniformly mixed, and carbonized at 500°C for 2 h, and then heated to 1200°C, and a mixed gas of phosphine and nitrogen (volume ratio, phosphine:nitrogen=1:10) was introduced at a total flow rate of 500 mL / min for 30 min; and then the obtained composite coke material was graphitized at 3200°C for 24 h to obtain a graphite material.

[0043] Step S2: 5 g of lithium polyvinylbenzenesulfonate, 5 g of molybdenum sulfide were added into 100 g of ethyl butyl ether to configure a solution, and then 5 g of styrene-acrylic acid copolymer, 100 g of graphite material were uniformly dispersed; spray drying was performed, wherein the drying medium inlet temperature was 220 ℃, the outlet temperature was 80 ℃, the flow rate was 0.2 kg / h, the drying time was 5 h, and the negative electrode active material was obtained.

[0044] Comparative Example 1 The preparation method of the present comparative example was basically the same as that of Example 1, and the only difference was that the present comparative example did not add an organic titanium-based crosslinking agent in step S1, and the other preparation conditions and parameters were the same as those of Example 1.

[0045] Comparative Example 2 The preparation method of the present comparative example was basically the same as that of Example 1, and the only difference was that the present comparative example omitted step S2.

[0046] Comparative Example 3 The preparation method of the present comparative example was basically the same as that of Example 1, and the only difference was that the present comparative example did not pass phosphorane gas in step S1. Specifically, step S1 of the present comparative example was as follows: 100 g of high-sulfur petroleum coke, 50 g of isotropic coke, 5 g of an organic titanium-based crosslinking agent, and 1 g of high-temperature pitch, 1 g of isophthalic acid type vinyl unsaturated resin were uniformly mixed, and then heat treated at 300 ℃ for 12 h, and then heated to 1000 ℃, and nitrogen gas was passed at a gas flow rate of 100 mL / min for 300 min, and then the obtained composite coke material was heated to 2800 ℃ for high-temperature graphitization for 48 h to obtain a graphite material.

[0047] Comparative Example 4 The preparation method of the present comparative example was basically the same as that of Example 1, and the only difference was that the present comparative example used high-titanium slag to replace the organic titanium-based crosslinking agent when preparing the negative electrode active material. The preparation steps of the present comparative example were as follows: Preparation of negative electrode active material from composite coke raw material: Step S1, 100 g of high-sulfur petroleum coke, 100 g of isotropic coke, 10 g of high-titanium slag, and 3 g of medium-temperature pitch, 3 g of bisphenol A type vinyl unsaturated polyester were uniformly mixed, and then heat treated at 400 ℃ for 6 h, and then heated to 1100 ℃, and a mixed gas of phosphorane and nitrogen (volume ratio, phosphorane:nitrogen=3:10) was passed at a total flow rate of 300 ml / min for 6 h, and then the obtained composite coke material was heated to 3000 ℃ for high-temperature graphitization for 48 h to obtain a graphite material.

[0048] Step S2, 3g of lithium 4-methylbenzenesulfonate and 3g of molybdenum sulfide were added to 120g of ethyl ether organic solvent to form a solution, and then 3g of polyisobutylene succinate and 100g of graphite material were uniformly dispersed; spray drying was performed, wherein the inlet temperature of the drying medium was 220°C, the outlet temperature was 80°C, the flow rate was 0.2kg / h, the drying time was 5h, and the negative electrode active material was obtained.

[0049] Performance test: (1) Performance test of negative electrode active material SEM test: the negative electrode active material prepared in Example 1 was subjected to SEM test, and the results are shown in FIG. 1. Figure 1 As can be seen from FIG. 1, the material presents a single particle structure with a particle size of 8-12μm and slight adhesion. Figure 1

[0050] Physicochemical property test: the specific surface area, tap density, and 2T compaction density of the negative electrode active material prepared in each example and comparative example were tested according to the test method in the standard GB / T-24533-2019 “Graphite-based negative electrode material for lithium ion battery”. The diffusion coefficient of the powder material was tested by constant current intermittent titration method (GITT). The powder resistivity was tested by four-probe tester, and the powder graphite orientation degree (OI) value was tested by XRD; the specific test results are shown in Table 1. Among them, comparative example 2 omitted step S2, so the graphite material prepared in comparative example 2 was directly tested.

[0051]

[0052] As can be seen from Table 1, the diffusion coefficient and tap density of the negative electrode active material prepared in Examples 1-3 are obviously better than those of Comparative Examples 1-4. The reason is that when the negative electrode active material is prepared in Examples 1-4, the titanium-based crosslinking agent added improves the adhesion of the material and improves the density, and the shell coated with lithium phenyl and molybdenum sulfide improves the insertion and extraction rate of lithium ions in the charging and discharging process, and improves the diffusion coefficient; at the same time, the isotropic coke is mixed to reduce the expansion and reduce the OI value of the powder.

[0053] (2) Button cell test According to the following method, button cells were assembled: the negative electrode active material of Examples 1-3 and Comparative Examples 1 and 3-4, and the graphite material prepared in Comparative Example 2 were respectively used as the negative electrode material, and lithium sheet, electrolyte and separator were assembled into button cells in an argon glove box with water content less than 0.1ppm. Among them, the separator is celegard 2400; the electrolyte is a solution of LiPF6, the concentration of LiPF6 in the electrolyte is 1mol / L, and the solvent is a mixed solution of ethylene carbonate (EC) and dimethyl carbonate (DMC) obtained by mixing in a weight ratio of 1:1. ​

[0054] The performance of each button cell was tested by a blue light tester, and the test conditions were as follows: Rate performance: 0.1C rate charge and discharge, voltage range 0.005V-2V, stop after 3 cycles, then test the discharge specific capacity of each button cell under 1C condition, and calculate the rate performance of 1C / 0.1C.

[0055] Cycle performance: 1C / 1C charge and discharge rate, voltage range 2.5V-3.65V, test the cycle performance of the battery after 1000 cycles at a temperature of 25±3℃.

[0056] Full charge expansion rate: dissect the full charge electrode sheet of the negative electrode, and test its full charge expansion. The specific test results are shown in Table 2.

[0057]

[0058] As can be seen from Table 2, the discharge capacity and initial efficiency of the button cell using the graphite composite material of Examples 1-3 are significantly higher than those of Comparative Examples 1-4. The reason is that the negative electrode material prepared in the examples has a high diffusion coefficient, and the surface of the negative electrode active material is coated with phenyl lithium, which reduces the irreversible capacity of the negative electrode active material, thereby improving the initial efficiency of the button cell, and also improving the cycle performance of the button cell.

[0059] (3) Performance test of soft package battery The negative electrode active material prepared in Examples 1-3 and Comparative Examples 1, 3-4 and the graphite material prepared in Comparative Example 2 were used as negative electrode materials, and were assembled into 5Ah soft package batteries together with the positive electrode active material lithium iron phosphate, electrolyte and separator. The separator was celegard 2400, and the electrolyte was LiPF6 solution (the solvent was a mixture of EC and DEC at a volume ratio of 1:1, and the concentration of LiPF6 was 1.1 mol / L).

[0060] The cycle performance of each soft package battery was tested, and the specific test conditions were as follows: 1C / 1C charge and discharge rate, voltage range 2.5V-3.65V, test the 500 cycle, 1000 cycle performance of the battery at a temperature of 25±3℃. The specific test results are shown in Table 3.

[0061]

[0062] As can be seen from Table 3, when the negative active materials prepared in Examples 1-3 are used as the negative electrode, the cycle performance of the corresponding soft package batteries is obviously better than that of the comparative example, and the reason is that the negative active materials of the examples have low expansion rate and high diffusion coefficient, which can improve the structural stability of the negative electrode. At the same time, the surface of the material is coated with phenyl lithium compound, which provides lithium ions in the charging and discharging process, reduces the loss of lithium ions in the cycle process, and thus improves the cycle performance of the soft package battery.

[0063] The above description is merely a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any person skilled in the art can easily think of various equivalent modifications or replacements within the technical range disclosed in the present application, and these modifications or replacements shall be encompassed within the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the protection scope of the claims.

Claims

1. A method for preparing a negative electrode active material, characterized in that, Includes the following steps: High-sulfur petroleum coke, isotropic coke, organotitanium-based crosslinking agent and binder are mixed and then carbonized at 300℃~500℃. After carbonization, the temperature is raised to 1000℃~1200℃ and then phosphine is introduced to dope phosphorus into the carbonized material to obtain phosphorus-doped graphite precursor. The phosphorus-doped graphite precursor is graphitized to obtain phosphorus-doped graphite. The phosphorus-doped graphite was immersed in an organic solution containing molybdenum sulfide and lithium benzenesulfonate compounds, and then dried to obtain the negative electrode active material.

2. The preparation method according to claim 1, characterized in that, The mass ratio of the high-sulfur petroleum coke, the isotropic coke, the organotitanium-based crosslinking agent, and the binder is 100:(50-200):(5-20):(2-10).

3. The preparation method according to claim 1, characterized in that, The binder is selected from asphalt and unsaturated resin; the asphalt is selected from medium-temperature asphalt and high-temperature asphalt; the unsaturated resin is selected from at least one of bisphenol A type vinyl unsaturated polyester and isophthalic acid type vinyl unsaturated resin; the mass ratio of the asphalt to the unsaturated resin is 1:(0.2-5).

4. The preparation method according to any one of claims 1 to 3, characterized in that, The method for introducing phosphine includes: mixing phosphine with nitrogen gas, and then introducing the mixed gas; the volume ratio of phosphine to nitrogen gas is (1-5):10; the total flow rate of the mixed gas is 100 mL / min to 500 mL / min; and the time for introducing the mixed gas is 30 min to 300 min.

5. The preparation method according to any one of claims 1 to 3, characterized in that, The preparation method satisfies at least one of the following conditions: (1) The carbonization time is 2h to 12h; (2) The graphitization time is 2h to 12h; (3) The graphitization temperature is 2800℃~3200℃.

6. The preparation method according to any one of claims 1 to 3, characterized in that, The preparation method of the organotitanium-based crosslinking agent includes the following steps: Titanate, ethylene glycol, organic acid and hydroxybenzaldehyde compounds are mixed in a mass ratio of (5-15):100:(10-30):(10-30), and then reacted at 50℃-100℃ for 2-12 hours; filtered and vacuum dried to obtain the organotitanium-based crosslinking agent. The titanate is selected from one of tetrabutyl titanate, tetraisopropyl titanate, tetra-2-methyl-2-butanol titanate, and tetrapropyl titanate. The organic acid is selected from one of benzoic acid, p-aminobenzenesulfonic acid, tartaric acid, oxalic acid, malic acid, citric acid, and ascorbic acid; The hydroxybenzaldehyde compounds are selected from one of m-hydroxybenzaldehyde, 2,5-dihydroxybenzaldehyde, 3,4-dihydroxybenzaldehyde, 2,3-dihydroxybenzaldehyde, 2-hydroxy-5-methylbenzaldehyde, and 2-hydroxy-4-methylbenzaldehyde.

7. The preparation method according to any one of claims 1 to 3, characterized in that, The preparation method satisfies at least one of the following conditions: (1) The lithium benzenesulfonate compound is selected from one of lithium 4-methylbenzenesulfonate, lithium 3-(diphenylphosphino)benzenesulfonate, lithium 4-(diphenylphosphino)benzenesulfonate, and lithium polyvinylbenzenesulfonate; (2) The organic solvent in the organic solution is selected from one of diethyl ether, dipropyl ether, diisopropyl ether, ethyl butyl ether, dibutyl ether, dipentyl ether, and diisopentyl ether; (3) The organic solution also contains a dispersant; the dispersant is selected from one of polyisobutylene succinate, propylene glycol methyl ether acetate and styrene-acrylic acid copolymer; (4) The mass concentration of molybdenum sulfide in the organic solution is 1 wt% to 10 wt%; (5) The mass concentration of lithium benzenesulfonate in the organic solution is 1wt% to 10wt%.

8. A negative electrode active material, characterized in that, The negative electrode active material is prepared by the preparation method according to any one of claims 1 to 7; or, the negative electrode active material includes a core and a shell disposed on the surface of the core, the core including phosphorus-doped graphite, and the shell including molybdenum sulfide and lithium benzenesulfonate compound.

9. The negative electrode active material according to claim 8, characterized in that, Based on the total mass of the negative electrode active material being 100%, the mass percentage of the shell layer in the negative electrode active material is 2wt% to 5wt%.

10. A battery, characterized in that, The battery includes a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode includes a negative electrode active material prepared according to any one of claims 1 to 7, or the negative electrode includes a negative electrode active material according to any one of claims 8 to 9.

Citation Information

Patent Citations

  • Porous-carbon-nanosheet-based supercapacitor and preparation method thereof

    CN107665775A

  • Graphite composite material and preparation method and application thereof

    CN116706010A

  • Graphite negative electrode material and preparation method thereof, negative electrode plate and lithium ion battery

    CN117691091A

  • Negative active material, negative pole piece, lithium ion battery and electric device

    CN120709339A

  • Process for the pre-treatment of mass-produced parts for chipless cold forming

    DE2254378A1

Cited By

  • Graphite composite material, preparation method thereof and lithium ion battery

    CN121905847A